Low clinical conversion rate in clinically isolated syndrome patients – diagnostic benefit of McDonald 2010 criteria?. (2nd December 2017) - Rosenkranz, S. C.; Kaulen, B.; Neuhaus, A.; Siemonsen, S.; Köpke, S.; Daumer, M.; Stellmann, J.‐P.; Heesen, C.
Abstract : Background and purpose: New diagnostic criteria of multiple sclerosis (MS) increase the number of patients being diagnosed with MS whilst a substantial part might not convert to clinically definite MS (CDMS). The diagnostic accuracy of the McDonald 2005 and 2010 criteria for conversion to CDMS was evaluated in an unselected cohort of patients in whom an MS diagnostic work‐up was decided. Methods: Clinical, magnetic resonance imaging and cerebrospinal fluid data were analysed for all patients who presented with symptoms suspicious for MS at the university based MS outpatient clinic between 2006 and 2010 ( n = 165). Results: Follow‐up was available for 131 patients. During the mean follow‐up period of 2 years, 19% of patients developed CDMS whereas 64% of the patients fulfilling McDonald 2010 criteria did not convert to CDMS. Conclusion: The low clinical conversion rate indicates that the new diagnostic criteria may increase the incidence of MS cases with a less active disease course. Abstract : Click here to view the accompanying paper in this volume.